233k views
1 vote
Using the method of completing the square, put each circle into the form


(x-h)^(2) + (y-k)^(2) = r^(2)
Then determine the center and radius of each circle


4x^(2) -4x + 4y^(2) - 59 = 0

User Changhwan
by
4.9k points

1 Answer

5 votes

Answer:

Standard form:
(x-(1)/(2))^2 + (y-0)^2 = 15

Center:
((1)/(2), 0)

Radius:
r =√(15)

Explanation:

The equation of a circle in the standard form is


(x-h)^(2) + (y-k)^(2) = r^(2)

Where the point (h, k) is the center of the circle

To transform this equation
4x^(2) -4x + 4y^(2) - 59 = 0 this equation in the standard form we use the method of square.

First, we group similar variables


(4x^(2) -4x) + (4y^(2)) - 59 = 0

Divide both sides of equality by 4


(x^(2) -x) + (y^(2)) - 14.75 = 0

Now we complete square for variable x.

Take the coefficient "b" that accompanies the variable x and divide by 2. Then, elevate the result to the square:


b =-1\\\\(b)/(2)= (-1)/(2)= -(1)/(2)\\\\((b)/(2))^2=  (-(1)/(2))^2 = (1)/(4)

Now add
((b)/(2))^2 on both sides of the equality


(x^(2) -x +(1)/(4)) + (y^(2)) - 14.75 = ((1)/(4))

Factor the expression and simplify the independent terms


(x-(1)/(2))^2 + (y^(2)) = 15


(x-(1)/(2))^2 + (y-0)^2 = 15

Then


h =(1)/(2)\\\\k=0

and the center is
((1)/(2), 0)

radius
r =√(15)

User Harshit Agarwal
by
5.3k points